(untitled) - Xiu, Zongchang (Beijing, China, 2002)
Melons, fruits and vegetables can be used for prevention and treatment of various diseases. The recipes, both ancient and modem, contained in this book have been proved to be effective for treating more than 100 diseases in the medical, surgical, gynecological, pediatric, dermatological and ENT spheres. This book is a handy reference guide to help medical workers with family health care and treatment of patients as well as for medical research.
Keywords: Medicine, Chinese